Handbook of software quality assurance - McManus, James I.; Schulmeyer, G. Gordon (Upper Saddle River, NJ : Prentice Hall, 1999)
In this guide, sixteen of the world's leading SQA experts share their practical experience with the full range of techniques available for managing software quality. Discover the best ways to organize, staff and improve your software quality organization. Learn how to make the most of inspections, software configuration management, Pareto charts, metrics, statistical methods, CASE tools and other key SQA tools and approaches.
Includes bibliographical references and index.
oif 19/02/15
Loan
Keywords: Computer software; Computer software - quality control